Discovering Panel of Autoantibodies for Early Detection of Lung Cancer Based on Focused Protein Array - Jiang, Di; Zhang, Xue; Liu, Man; Wang, Yulin; Wang, Tingting; Pei, Lu; Wang, Peng; Ye, Hua; Shi, Jianxiang; Song, Chunhua; Wang, Kaijuan; Wang, Xiao; et al. (Frontiers in Immunology, 2021)
Substantial studies indicate that autoantibodies to tumor-associated antigens (TAAbs) arise in early stage of lung cancer (LC). However, since single TAAbs as noninvasive biomarkers reveal low diagnostic performances, a panel approach is needed to provide more clues for early detection of LC. In the present research, potential TAAbs were screened in 150 serum samples by focused protein array based on 154 proteins encoded by cancer driver genes. Indirect enzyme-linked immunosorbent assay (ELISA) was used to verify and validate TAAbs in two independent datasets with 1054 participants (310 in verification cohort, 744 in validation cohort). In both verification and validation cohorts, eight TAAbs were higher in serum of LC patients compared with normal controls. Moreover, diagnostic models were built and evaluated in the training set and the test set of validation cohort by six data mining methods. In contrast to the other five models, the decision tree (DT) model containing seven TAAbs (TP53, NPM1, FGFR2, PIK3CA, GNA11, HIST1H3B and TSC1), built in the training set, yielded the highest diagnostic value with the area under the receiver operating characteristic curve (AUC) of 0.897, the sensitivity of 94.4% and the specificity of 84.9%. The model was further assessed in the test set and exhibited an AUC of 0.838 with the sensitivity of 89.4% and the specificity of 78.2%. Interestingly, the accuracies of this model in both early and advanced stage were close to 90%, much more effective than that of single TAAbs. Protein array based on cancer driver genes is effective in screening and discovering potential TAAbs of LC. With the TAAbs signature of TP53, NPM1, FGFR2, PIK3CA, GNA11, HIST1H3B and TSC1 is excellent in early detection of LC and they might be new target in LC immunotherapy.